1969
DOI: 10.1159/000130040
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication studies of human D-group chromosomes in satellite associations

Abstract: DNA replication studies were carried out on metaphase plates showing satellite associations to determine the association of individual D chromosomes. In a total of 279 D chromosomes involved in satellite associations and identified by autoradiography, it was found that the association of the three members of the D chromosomes was random. In D/D associations no prevalence of homologous combination was observed. In addition, a case of D trisomy and three cases with t(GqDq) (from two unrelated families) were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1970
1970
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 9 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…As shown in earlier studies (Nakagome, 1969;Shaw et al, 1969), and as confirmed by the present study on 2 cases with t(13ql4q), satellite association is generally random. However, in some specific instances it may be non-random, as suggested by our 2 cases with t(l4qGq).…”
supporting
confidence: 91%
See 3 more Smart Citations
“…As shown in earlier studies (Nakagome, 1969;Shaw et al, 1969), and as confirmed by the present study on 2 cases with t(13ql4q), satellite association is generally random. However, in some specific instances it may be non-random, as suggested by our 2 cases with t(l4qGq).…”
supporting
confidence: 91%
“…Further, an increased incidence of satellite association has been observed in families with translocation and multiple cases of mosaicism (Zeliweger, Abbo, and Cuany, 1966; Abbo, Zeliweger, and Cuany, 1966).Recently, Nakagome (1969) and Shaw, Craig, and Ricciuti (1969) showed that, in normal subjects, the members of the three pairs of D group chromosomes were randomly involved in satellite associations. However, these findings do not preclude the possibility that there are non-random patterns of associations in people who are 'predisposed' to translocation or non-disjunction.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…These examples suggest that, in spite of a frequent NOR (satellite) association (Nakagome, 1969;van Hemel, 1971), Rabl configuration (Cremer et al, 1982), telomere-telomere attachment (Sved, 1966;Ashley and Pocock, 1981), or the so-called bouquet configuration, telomeres are usually protected safely from chromosomal rearrangements. However, telomeric fusions occur often under some specific conditions such as long-term cell culture, tumoriogenesis, or infection by virus/transposon like or unknown factors other than ionizing radiation.…”
Section: ) a Possible Biological Significance Of The Fusion Burst Inmentioning
confidence: 99%